Factors Affecting Pork Consumer Demand During The Covid- 19 Pandemic in Medan City, North Sumatra Province - Suryadi. G; G. A. W. Siregar; Yunilas; H. Hutauruk (Jurnal Peternakan Integratif, 2023)
At the end of 2019, people in Medan City were shocked by the death of thousands of pigs in several districts in North Sumatera caused by African Swine Fever (ASF). In early March 2020, the government enacted the Large-Scale Social Restrictions (PSBB) policy due to the Covid-19 pandemic. These conditions caused an economic contraction marked by the growth of the national Gross Domestic Product (GDP) which fell sharply in the second quarter of 2020 against the second quarter of 2019 by 5.32% (y-on-y). This study aims to analyze the availability and price of pork and the factors that affect consumer demand for pork during the Covid-19 pandemic in Medan City. The research location consists of six traditional markets in Medan City that sell pork, namely Kanpung Lalang Market, Sunggal Market, Melati Market, Sambu Market, Sambas Market, and Sukaramai Market with purposive sampling method. There were 80 respondents. The data collection methods used were observation, interview, and literature study. The data processing and analysis method used is the Classical Assumption Test and Model Fit Test. The results showed that the total demand for pork before the Covid-19 pandemic was 98 kg while the demand for pork during the Covid-19 pandemic decreased to 40 kg. The decrease in demand for pork is due to the increase in pork prices caused by the outbreak of ASF disease in pigs in North Sumatra. However, the purchasing power of the people of Medan City decreased due to a decrease in income caused by Covid-19. Based on the results of the study, it can be concluded that during the Covid-19 pandemic there was a very drastic decrease in demand for pork with a percentage reaching more than 50%